Ali-Pasha Rizvanbegović Stočević’s Deeds of Endowment and Testament (Prilozi za orijentalnu filologiju, 2017)
This paper brings a brief biography of the Rizvanbegovićs, one of the most renowned Herzegovina 19th century families. Nine deeds of endovvment (waqfnamahs) of Ali-pasha Rizvanbegović relating to his buildings in Stolac, Mostar, Buna, then in Široki Brijeg, Foča, and other places in Bosnia and Herzegovina are given here as translations in extenso. Also presented is the translation of Ali-pasha’s testament (wassiyetnamah). Along with the translations, there are the facsimiles of the originals being kept in Istanbul in the family of Husref Gered, one of Ali-pasha’s grandsons.